Mobile Application for Behavioral and Social Skills Learning for Autism Children using Facial Expression Recognition - Hao Zhan, Gan; Ramachandiran, Chandra Reka (International Journal of Psychosocial Rehabilitation, 2019)
Autism Spectrum Disorder is a neurodevelopment disease which is prevalent recently. This study addressed the possible factors that cause ASD, as well as the treatment for the disorders. However, with the implementation of current technology, this study aims to propose a mobile application as a solution that helps autism children for behavioral and social skills learning by using facial expression recognition, which can provide brief understanding of basic facial expression and emotion to children with ASD and slowly develop their social skills. Overall, the proposed mobile application is able to detect facial expression and emotion using live feed from camera of the mobile device. Besides, there is also simulation of certain environment to represent the daily life interaction with people which could aid in developing social communication skills.